EduVizBR: A decision support system for Brazilian high school students' performance analysis - Fernandes, Chrystinne; Vieira, Dienert; Barros, Tassiane; Shay, Aian; Freitas, Nicksson; Vinuto, Tiago (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2022: Anais do XXXVII Simpósio Brasileiro de Bancos de Dados, 2022)
Due to the explosive growth of educational data, more assistant tools are demanded by Educational managers to mine and filter strategic knowledge into massive databases. In this paper, we present the EduVizBR, a decision support tool designed to assist managers in analyzing the students' performance in the Brazilian national exam (ENEM). The EduVizBr allows managers to explore a massive volume of integrated educational data by narrowing their analyses according to the most relevant impact factors presented in the literature, year of interest, and school subjects. In our case study, we analyzed how gender impacts students' grades in all Brazilian states and the influence of parents' educational attainment and parents' professions on their children's grades.